Bullying, supervisor support, relaxation, and personal and work outcomes: Testing a moderated mediation model. (28th April 2021) - Gillet, Nicolas; Fernet, Claude; Colombat, Philippe; Cheyroux, Pierre; Fouquereau, Evelyne
Abstract: Aim: To test a mediated moderation model in which bullying and supervisor support interact to predict nurses' personal and work outcomes with relaxation during off‐job time mediating these effects. Background: Bullying is a pervasive problem in the nursing profession. We integrate and extend past research addressing the question of how bullying and perceived supervisor support affect nurses' functioning. Method: Cross‐sectional data were collected from a sample of 290 nurses who completed measures of bullying, perceived supervisor support, relaxation, need for recovery, sleeping problems, job satisfaction, emotional exhaustion and work performance. Results: Results revealed that bullying was significantly linked to job satisfaction, sleeping problems, need for recovery and emotional exhaustion through relaxation, but only among nurses who perceived high levels of supervisor support. Conclusion: These results revealed that high supervisor support may be detrimental for nurses adding up to a negative cycle of stressors to maladaptive outcomes through lack of relaxation. Implications for Nursing Management: Health care organisations and managers should consider addressing work environment factors, such as bullying, in addition to supervisor support in their efforts to facilitate the positive effects of nurses' relaxation during non‐work time.